Dietary Strawberries Improve Insulin Resistance in Adults with the Metabolic Syndrome. (29th May 2020) - Davis, Dustin; Scofield, Hal; Betts, Nancy; Izuora, Kenneth; Basu, Arpita
Abstract: Objectives: Dietary berries have been shown to lower cardio-metabolic risks in clinical trials. We examined the dose-response effects of two dietary achievable doses of strawberries on low-density lipoprotein cholesterol (LDL-C) and insulin resistance in adults with metabolic syndrome. Methods: In this 14-week randomized controlled crossover study, adults with metabolic syndrome were assigned to one of the three arms for 4 weeks separated by a one-week washout period: control powder, one serving strawberries (13 g powder/day), and 2.5 servings strawberries (32 g powder/day). The freeze-dried powders were blended in water, and participants consumed half the daily dose in the morning and half in the evening. Participants were instructed to follow their usual diet and lifestyle while refraining from consuming other berries and related products throughout the study. Results: Thirty participants completed all three phases of the trial (baseline profiles: weight: 90.8 ± 22.4 kg, BMI: 33.1 ± 4.2 kg/m 2, waist circumference: 109 ± 12.5 cm, HbA1c : 5.8 ± 0.2%). Outcome measures were analyzed using a multivariate analysis of variance with statistical significance set at P < 0.05. Preliminary data indicate a significant reduction in the homeostatic model of assessment of insulin resistance (HOMA-IR) following the 2.5 servings strawberries when compared to the 1 serving strawberry and control phases. Glucose and conventional lipid profiles did not differ among groups. Small LDL particle concentration (nuclear magnetic resonance-determined) was significantly decreased in the high dose strawberry group compared to baseline and one-serving group ( P < 0.05). Conclusions: These data suggest that consuming strawberries at 2.5 servings daily for four weeks significantly improved insulin resistance and LDL particle profile in adults with metabolic syndrome. Funding Sources: Supported by the California Strawberry Commission.